Implementasi Infrared Barrier Obstacle Sensor Menggunakan Modul Hw-201 Pada Smart Car Robot Line Follower - Amin Widodo; Toni Rahmat Wahyu; Ranti Imawati; Febiyana Firdaus; Haris Priazun; Rejeki, Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Pamulang, 2024)
This research discusses the implementation of an infrared barrier obstacle sensor using the HW-201 module on a smart car robot line follower. The main aim of this research is to improve the ability of the smart car robot line follower to detect and follow lines on a predetermined path. This system is designed to use an infrared barrier obstacle sensor installed on the front of the line follower robot smart car facing downwards to detect and follow lines along the movement path. The method used includes hardware design consisting of the HW-201 module, microcontroller and drive motor, as well as software development to control the response of the smart car robot line follower to the detected line. The test results show that the smart car robot line follower is able to detect and follow lines with high accuracy, thereby increasing efficiency and reliability in following the line. It is hoped that this implementation can become the basis for further development of robotic systems that require automatic navigation capabilities. And these results show that the HW-201 IR sensor is a suitable option for robotics applications that require the ability to detect and avoid obstacles.